Geophysical exploration technology : applications in lithological and stratigraphic reservoirs - Li, Ming (Geophysicist); Zhao, Yimin (Elsevier, 2014)
"Based on theories and exploration technologies of lithological and stratigraphic reservoirs, this book systematically summarized a series of geophysical exploration methods and techniques corresponding to different types of lithological and stratigraphic reservoirs by analyzing more than thirty successful cases. From the applying aspect, this book also briefly introduced the main geophysical principles and methods related to the exploration of lithological and stratigraphic reservoirs, discussed optimal analyzing procedures and some key issues, and evaluated the applying conditions, the advantages and disadvantages of some mainstream software. Finally, in order to discuss different geophysical exploration methods used for the identifications of different types of lithological and stratigraphic reservoirs in different geological conditions, we specially introduced three successful cases in detail including a certain low-abundance structural and lithological reservoir in eastern China, a stratigraphic carbonate reservoir in western China and a deep-buried volcanic gas reservoir in northern China"-- Provided by publisher.
Keywords: Hydrocarbon reservoirs.; elektronické knihy; electronic books